Patient Loyalty in the Digital Age: Literature Study of Digital Services and Digital System Security - Basrowi; Wiguna, Wahyu; muti'ah, Eva (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2023)
In today's digital era, many things are done through the use of technology such as the use of the internet, online-based services and so on. Health services are no exception, customers always want fast, responsive and easy-to-reach services, so digital services are loved by the public. The level of speed of service, quality of service and safety in service are the main things desired by customers to achieve a level of patient satisfaction that encourages patient loyalty. The purpose of this study was to determine the factors that influence patient loyalty in terms of digital service quality and digital system security to achieve patient satisfaction. The method used is literature by reviewing various latest literature materials starting from journals, books, proceedings, and various sources both online and offline. To improve the quality of the results of the study, focus group discussions were also conducted to obtain various inputs, corrections and various suggestions from the FGD participants. The results of the analysis based on theoretical studies can be concluded that, factors that influence patient loyalty include digital service quality, and digital system security. The novelty of this research is that it is able to show theoretically that patient loyalty can be directly influenced by the quality of digital services and the security of digital systems both directly and through patient satisfaction.